OMNICHANNEL MARKETING STRATEGY: BRIDGING THE GAP BETWEEN ONLINE AND OFFLINE CUSTOMER EXPERIENCE - Nyi Dewi Puspitasari; Silvia Ekasari; Era Purike (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
Omnichannel marketing strategies have become a major focus for many companies in their efforts to optimize customer experience in the digital age. The research method used is literature. The results show that an effective omnichannel strategy can significantly increase customer satisfaction, loyalty, and customer lifetime value. However, its implementation presents challenges such as technology integration and organizational culture change.